The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/esp.5115
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic landforms and geomorphic features associated with impact structures: Observations at the Dhala structure, north‐central India

Abstract: Geomorphological study of some of the just more than 200 known terrestrial impact structures has demonstrated that despite extensive degradation, important geomorphological keys, such as drainage pattern, topographic signatures, erosional landforms, and depositional features, can still be assessed. They can provide possible indicators to assist in the recognition of further impact structures, especially on Precambrian shields and cratonic landmasses. This study documents the surface features and landforms of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 101 publications
0
6
0
Order By: Relevance
“…The impact melt rocks of the Dhala impact structure show minor postimpact alteration (Pati et al., 2010; Singh et al., 2021a). However, these postimpact hydrothermal events do not significantly affect the magnetic fabrics of the impact melt rock (Singh et al., 2021b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact melt rocks of the Dhala impact structure show minor postimpact alteration (Pati et al., 2010; Singh et al., 2021a). However, these postimpact hydrothermal events do not significantly affect the magnetic fabrics of the impact melt rock (Singh et al., 2021b).…”
Section: Discussionmentioning
confidence: 99%
“…These fractured basement granitoids possess a ∼12 m thick suevite horizon in between (Pati et al., 2019). The fractured target basement of the Dhala impact structure contains about 201 large to small outcrops of the monomict lithic breccia (Singh et al., 2021b), which spread over an area of about 45 km 2 in the outermost annular zone of the Dhala impact structure. The fractured target basement is overlain by the impact melt rock.…”
Section: Geological Settingmentioning
confidence: 99%
“…The annular region between the CEA and the monomict breccia ring is mainly occupied by sub‐horizontal intercalated purplish‐brown siltstone and greenish‐white sandy siltstone, together with pockets of conglomerate lenses within a clastic matrix (Pati, Reimold, et al., 2008). Despite the prolonged erosion and multiple post‐impact tectono‐thermal activities in the region, the impactites of the Dhala structure are relatively well preserved as revealed by the field observations (Pati et al., 2010; Singh et al., 2021). The presence of shatter cones, impact‐diagnostic microscopic shock metamorphic features, and the chemical signature of extraterrestrial components within impact melt breccia also confirmed the well‐shielded nature of the Dhala structure (Pati et al., 2019 and references therein).…”
Section: Geological Setting Of the Dhala Impact Structurementioning
confidence: 98%
“…Nevertheless, the precise age of the Dhala impact event is not determined so far and is stratigraphically constrained between 2.5 and 1.7 Ga corresponding to the ages of the target granitoids and the post‐impact sediments of the Vindhyan Supergroup, respectively (Pati et al., 2010). In the Dhala area, the CEA is surrounded by a ring of >200 monomict breccia outcrops occurring in the outermost annular region of the structure (Singh et al., 2021). These breccia bodies mostly comprise sheared, fractured, and extensively brecciated fragments of the target rocks.…”
Section: Geological Setting Of the Dhala Impact Structurementioning
confidence: 99%
“…One of the most interesting landforms in the Bundelkhand craton in peninsular India is the Dhala impact crator, which has attracted the attention of geologists for several decades (Pati et al, 2008(Pati et al, , 2015(Pati et al, , 2017Sinha et al, 2011). In the most recent paper, Singh et al (2021) have documented the surface features and landforms of the Dhala crator. With an age bracketed between 1.7 and 2.5 Ga, the Dhala is The use of fractals should add a new dimension to understand the complex interaction of various geologic and geomorphic processes in topographic evolution.…”
Section: Peninsular Indiamentioning
confidence: 99%